Modeling the daytime energy balance of the topside ionosphere at middle latitudes. Issue 5 (24th May 2017) - Hsu, Chih‐Te; Heelis, Roderick A.
Abstract: Recently reported measurements from the Defense Meteorological Satellite Program (DMSP) indicate that the O + temperature in the topside ionosphere is dependent on the fractional H + density. This finding indicates that the mass‐dependent energy exchange rate between O + and H + plays an important role in the thermal balance of the topside ionosphere. In this study we utilize the SAMI2 model to retrieve both T H+ and T O+ and verify the previously observed dependence of ion temperature on ion composition. The model shows that in the topside at middle latitudes when a single ion is dominant, O + or H + is heated by electron collisions and cooled by conduction as expected. However, in the intervening altitude region where both O + and H + are present, O + is heated by collisions with H + and cooled by conduction, while H + is heated by collisions with electrons and cooled by collisions with O + . Key Points: Dependence of ion temperature on ion composition agrees with observations O + heated by electrons and H + H + cooled by collisions with O + and conduction